Sustainable healthy diets through food systems transformation – SHiFT Report of stakeholder consultation in Vietnam - Huynh Thi Thanh Tuyen; Pham, Huong Thi Mai; Duong, Thanh Thi (2022)
Information included in this report is extracted from group discussions session in the SHiFT workshop that was held on June 24, 2022 in Hanoi and the consultation event on November 24, 2022 in Thai Nguyen province co-chaired by Department of Cooperatives and Rural Development, Ministry of Agriculture and Rural Development and Alliance of Bioversity and CIAT.